Beyond the Hype: Local Engagement with AI-Generated Tourism Content - Nugroho, Vincentius Tangguh Atyanto; Soelistiyowati, Endang; Permatasari, Alfelia Nugky; Iban, Carlos (Jurnal Pariwisata Terapan, 2023)
Travelers seeking authentic interactions with nature and culture are increasingly interested in destinations managed by the local community. Amidst the rising number of communities offering similar traveling experiences, operators seek a way to promote their destination and its distinctiveness. One of the ways to accentuate the particularity and the status of a tourist spot is by doing an online promotion in English, and artificial intelligence seems to open a window for its possibilities. This research aims to reveal how residents perceive the use of AI, including ChatGPT, in promoting their community-based tourist destinations. Residents participating in the research were invited to express their feelings and reactions towards AI-generated texts promoting a community-managed destination in the area they reside. Their reactions revealed three states of emotion: insecurity, uncertainty, and inauthenticity. They also reported an inability to make an informed decision due to a lack of key knowledge and skills, rendering the use of AI unproductive.